Clinical study of urinary tract infection in children - Rao, K. Rajashekar; Gandhi, Sheetal Shantikumar; Kokiwar, Prashant R. (International Journal of Contemporary Pediatrics, 2016)
Background: The urinary tract infection is a significant cause for morbidity and mortality in children. The studies have shown that urinary tract infections in the early childhood are potentially dangerous, because they are the forerunners of the several renal diseases in the adulthood. Urinary tract infection is not isolated even but represents a complex situation which may follow a variety of courses during the life time of an individual. The objective was to study the incidence of urinary tract infection in children. Methods: The present study was carried out in Government general hospital, Gulbarga for a period of two years. In these prospective study 60 cases of urinary tract infection who were admitted in pediatric medical and pediatric surgical wards of Government general hospital with signs and symptoms suggestive of urinary tract infection were included in the study. Detailed history and complete clinical examination was done as per proforma. Routine urine examination was carried out. Results: The maximum numbers of cases were in the age group of 5-12 years. The male: female ratio was 1.3:1.70% came from rural area. Most of the cases were from lower classes. Maximum cases were noted in grade III malnutrition i.e. 30% and in grade I i.e. 23.3%. Maximum patients presented with fever i.e. 90% at the time of admission. Conclusions: The majority of the children in the present study were in the age group of 5-12 years. The male to female ratio was 1.3:1. Incidence of urinary tract infection was more in rural area than urban. Most of the children were from lower classes. Incidence was more in grade III malnourished children. Fever was the most common presenting symptom.